2001
DOI: 10.1111/j.1526-4610.2001.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Levels of Inflammatory Mediators in Migraineurs During Headache‐free Periods

Abstract: Objectives.-The present study investigated the peripheral inflammatory changes of the trigeminovascular system by measuring the inflammatory mediators leukotriene B 4 (LTB 4 ), prostaglandin E 2 (PGE 2 ), and thromboxane B 2 (TXB 2 ) in the nasal fluid, as well as saliva, of patients with migraine.Background.-Migraine has been hypothesized to be as a result of changes in the peripheral or central nervous system or both. It is still unclear whether peripheral changes in the trigeminovascular system are involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Urinary PG-F2a levels were significantly higher during migraine episodes than during headache-free periods. The similar levels of proinflammatory mediators during non-episodic periods in migraine patients and in healthy controls suggest the desensitization and lack of inflammation in nociceptors in the trigeminal vascular space (24). PG-F2a levels in patients with migraine start to increase during the first hour of a headache episode, peaking during the second hour and returning to normal levels after six hours; the algogenic and vasoactive features of PG-F2a that initiates migraine headaches have been highlighted (30).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Urinary PG-F2a levels were significantly higher during migraine episodes than during headache-free periods. The similar levels of proinflammatory mediators during non-episodic periods in migraine patients and in healthy controls suggest the desensitization and lack of inflammation in nociceptors in the trigeminal vascular space (24). PG-F2a levels in patients with migraine start to increase during the first hour of a headache episode, peaking during the second hour and returning to normal levels after six hours; the algogenic and vasoactive features of PG-F2a that initiates migraine headaches have been highlighted (30).…”
Section: Discussionmentioning
confidence: 98%
“…Urinary LT-E4 levels were found to increase in patients with inflammatory bowel diseases, especially during periods of active mucosal inflammation, suggesting that non-invasive measurements of urinary LT-E4 levels may indicate disease activation and that these patients may benefit from treatment with leukotriene inhibitors (23). A study measuring peripheral inflammatory mediators, including LT-B4, PG-E2 and thromboxane B2, in migraine patients showed that LT-B4 levels were lower during pain-free periods than during headaches (24). Concentrations of LT-B4 and LT-C4, which have been implicated in migraine pathophysiology, were found to increase during migraine episodes but to be normal between episodes (25).…”
Section: Discussionmentioning
confidence: 99%
“…Further development of analytic techniques may be of interest, especially for diseases in which dysfunction of the trigeminal system is known, for analysis of specific salivary compounds that are released into the saliva. In diseases such as (primary) headache syndromes including cluster headache (31) and migraine (10,(31)(32)(33)(34)(35)(36), but also in tension-type headache (36), and other diseases, analytical techniques that help qualifying and quantifying salivary (neuro)peptides including CGRP could be useful in elucidating pathophysiologic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine has also been shown to be associated with vascular inflammation that can be treated with nonsteroidal anti-inflammatories. 15,27 Inflammation produces oxygen-free radicals and it could be speculated that as inflammation in an acute or chronic migraine persists, an inability to respond to this with antioxidants may exacerbate attacks.…”
Section: Commentsmentioning
confidence: 99%